Re-experiencing Military Trauma in Groups: A Veteran’s Case Study - Cox, Daniel W.; Buchanan, Marla J.; Hoover, Stuart M.; Westwood, Marvin J. (Canadian Journal of Counselling and Psychotherapy, 2014)
Re-experiencing the distressing trauma(s) is a central component across trauma-focused psychotherapeutic orientations. Various orientations use different interventions to facilitate trauma re-experiencing. Via an in-depth case study, this article describes a military veteran’s experience and the benefits of a group-based intervention designed to facilitate re-experiencing through therapeutic enactment. Findings indicated that therapeutic enactment enabled the veteran to vividly re-experience the trauma, reducing trauma-related guilt and maladaptive self-schemas. Theoretical and applied implications are discussed.